"What's good fam?" : African digital sociality and notions of community and family in the UCKAR Facebook group - Dube, Hope Mutipeni (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
This study explores the digital sociality of the UCKAR Facebook group. This student Facebook group was formed during the 2015 #RhodesMustFall period. The acronym UCKAR stands for the "University Currently Known As Rhodes" and signifies hope for the transformation of the university. Qualitative interviews were conducted to investigate how UCKAR Facebook group understood and interpreted their sociality, i.e. what do they mean when they say "we" or "us" ; how such understandings emerged from group membership descriptions and interpersonal obligations as well as the actual social interactions and participation in the group through digital practices, that is, posting and commenting. A qualitative thematic analysis was undertaken through grouping together representations of various notions of the nature and purpose of their Facebook group as a social space, or its sociality. The findings revealed how various digital socialities co-exist in the same digital space. They reflect different ways in which group members can relate to each other meaningfully: either as fellow students, activists, student entrepreneurs and customers, caring community members or fellow revellers. I refer to these socialities as "Rhodent sociality" , "comrade sociality" , "hustle sociality" , "ubuntu sociality" and "groovist sociality" . These socialities are evidentially not mutually exclusive, and members can and do engage in multiple socialities within the group or shift amongst them depending on the situation. In this analysis, these socialities are linked to the existing scholarship on digital socialities. The findings suggest that the resilience to survive in an alien cultural space does not only demand a digital space that supports rational political resistance and practical tips to navigate the space as seen in the "comrade sociality" and "Rhodent sociality" . It also requires a digital space which can incorporate elements of communal care, economic survival and at times a Bakhtinian carnivalesque outlet to momentarily invert an unjust society . I call this kind of digital sociality a survivalist digital community, which is a form of digital sociality created by persons who need to survive a space that was not designed for people like them, and is underpinned by survivalist knowledge.
Keywords: Digital society; Facebook (Firm); Social media and college students -- South Africa -- Makhanda; Education, Higher Social aspects; Sociology Africa; College students Social life and customs; College students Social networks